Systematic Literature Review: The Effect of Green Innovation and Carbon Emission Disclosure on Financial Performance Moderated by Gender Diversity - Niken Ardelia Zamrizal; Vivi Nurul Alfia; Nadia Puspita Sari (Universitas 45 Surabaya, 2026)
This study aims to examine the effect of green innovation and carbon emission disclosure on corporate financial performance, moderated by gender diversity on the board of directors. The method used is a Systematic Literature Review (SLR) with a qualitative approach that analyzes various empirical studies published in reputable international journals. The review process follows a structured protocol, including identification, screening, eligibility, and synthesis of relevant literature. The results indicate that green innovation and carbon emission disclosure have a positive effect on financial performance through improved operational efficiency, enhanced corporate reputation, regulatory compliance, and increased investor confidence. Furthermore, gender diversity on the board strengthens this relationship by encouraging more inclusive, ethical, and sustainability-oriented decision-making processes. Boards with higher female representation tend to be more sensitive to environmental and social issues, leading to more effective implementation of sustainability strategies. This study confirms that the integration of environmental responsibility and board diversity within corporate governance frameworks can serve as a strategic mechanism to achieve sustainable competitive advantage, long-term financial performance, and stronger corporate social legitimacy in an increasingly environmentally conscious business environment.